Kontinuitas nilai-nilai pendidikan karakter ajaran ki hajar dewantara pada buku pelajaran bahasa jawa kelas V sekolah dasar - Yasmin Hanifa Aulia; Joko Daryanto; Sandra Bayu Kurniawan (Didaktika Dwija Indria, 2025)
The Javanese language textbook entitled "Sinau Basa lan Sastra Jawa Kanthi Mardika" shows the cultivation of character values according to Ki Hajar Dewantara's views on continuity in elementary school. This research aims to analyze the value of character education based on the views of Ki Hajar Dewantara. Using descriptive content analysis methods, this research analyzes how the value of character education is applied in the book. Data was obtained from the analysis of character values in textbooks and interviews with sources regarding Ki Hajar Dewantara's views. The research results show that the book "Sinau Basa lan Sastra Jawa Kanthi Mardika" instills character traits in accordance with the trikon concept based on Ki Hajar Dewantara, namely continuity, concentricity and convergence. This book shows strong emphasis on the value of integrity (28.95%), followed by the values of religion, justice and honesty (10.53% each). The diverse distribution of character values throughout the material shows efforts to instill various values through various forms of Javanese literature and culture. Furthermore, emphasizing nationalism (45.83%), as well as independence and mutual cooperation (20.83%). The higher the character value in certain material, such wayang stories and "geguritan", indicates that it is most effective in conveying various character values.